Cours Factoriser
Exercice d'application
Exercice : Calcul littéral

Soit l’expression : $A=(2x−5)(2x+4)−(2x−5)(x−3)$

1) Développer et réduire $A$.

2) Factoriser $A$.

3) Calculer la valeur de $A$ pour $x=3$. Puis pour $x=\dfrac{5}{2}$.

 

 

1) On a :

$A = (2x-5)(2x+4)-(2x-5)(x-3)$

$A = 4x^2 +8x -10x -20 -(2x^2-6x-5x+15)$

$A = 4x^2 +8x -10x -20-2x^2+6x+5x-15$

$A=2x^2+9x-35$

 

2) Factorisons : 

$A = (2x-5)(2x+4)-(2x-5)(x-3)$

$A=(2x-5)[(2x+4)-(x-3)]$

$A=(2x-5)(2x+4-x+3)$

$A=(2x-5)(x+7)$

 

3) Pour $x = 3$

$A_3 = (2\times 3-5)(3+7)$

$A_3=(6-5)\times 10$

$A_3=10$

 

Pour $x =\dfrac{5}{2}$

$A_{\frac{5}{2}}=(2\times \dfrac{5}{2}-5)(\dfrac{5}{2}+7)$

$A_{\frac{5}{2}}=(5-5)(\dfrac{5}{2}+7)$

$A_{\frac{5}{2}} = 0$